Menjadi Calon Guru: Studi Naratif Multitugas Mahasiswa PPL di SMP Negeri 12 Pematangsiantar - Dumaris E. Silalahi; Indah Anastasya Togatorop; Helena Zepania Samosir; Calvyn Sepanya Siregar; Cintya Pinta Nainggolan; Angelina Agustina Br Turnip; Falty Bastian Samosir; Cindy Yani Simorangkir; Kevin Christian Siagian (Yayasan Bayt Shufiya Nusantara, 2026)
This research aims to describe in-depth the dialectical process of professional identity formation among pre-service teachers through multidimensional involvement in partner schools. Teaching practicum (PPL) is often narrowly perceived as a mere instructional exercise; however, field realities reveal a complex and systemic multidimensional involvement. Utilizing a qualitative method with a narrative inquiry approach, this study explores the subjective experiences of a student teacher at SMP Negeri 12 Pematangsiantar. Data were collected through participant observation, practicum reports, and narrative reflections compiled over a twelve-week period. The results indicate that the student undergoes a process of